On the Subgroups of the Triangle Group *2p∞ - Miro, Eden Delight (Archīum Ateneo, 2012)
In this work, we discuss the low index subgroups of the triangle group *2p∞ (also called the extended Hecke group) which were derived using tools in color symmetry theory. Moreover, we present the low index subgroups of the index 2 subgroups of the extended modular group *23∞.